Contesting political theologies of Islam and democracy in Turkey*. Issue 2 (3rd May 2016) - Tepe, Sultan
Abstract: Turkey's secularism is often depicted as a system of control par excellence, pitting the secularist state against religion and ignoring the multiplicity of actors within the state as well as within religious sectors. A review of Turkey's main state institution, the Directorate of Religious Affairs (DRA) explains why models which reduce state–religious relations to a one-dimensional interaction of control or contestation are insufficient. Such models ignore the perplexing support of the DRA by religious groups due to their inability to identify the institution's dual role in maintaining the presence of Islam in the state structure and lending legitimacy to various religious groups. A pluralistic account of Turkey's secularism exposes its contradictions, such as DRA decisions that denounced state key secularist policies and the inadvertent outcomes of some state policies limiting Islamic groups. Exposing the paradoxical role of the state vis-à-vis religion the increasing number of woman employees in the DRA unleashed many unexpected changes in the institution, making it more open to once-marginalized women's groups and their critical theologies, and highlighting the limits of a dichotomous modeling of state–religion relations in Turkey and beyond.